(untitled) (Italian Journal of Public Health, 2007)
Introduction: Assessment of exposure to the airborne respirable particles (PM10) and polycyclic aromatic hydrocarbons (PAHs) of asphalt manufacturing and road paving workers in the Campania region (Italy). Materials and Methods: A study was carried out during 2006 and involved 5 firms producing and employing bitumen in road paving activities. The workers studied were categorized on the basis of their job as workers in bitumen manufacturing, in road paving and in workers not exposed at bitumen fume considered like controls. Results: In the manufacturing plants the average concentrations of airborne PM10 were 1125±445 ìg/m3 in the HMA manufacturing workers’ areas; 314±81 ìg/m3 in the process surveyors’ cabins and 92±27 ìg/m3 in the controls’ areas (administrative offices). Within the breathing zones of the worker, the average PAHs levels in air were as follows: 367±198 ng/m3 for HMA manufacturing workers; 348±172 ng/m3 for process surveyors; 21±2 ng/m3 for the controls. At the road paving sites the average airborne PM10 levels were 1435±325 ìg/m3 for roller operators; 1610±356 ìg/m3 for paver operators; 319±108 ìg/m for the controls (traffic controllers). PAHs in the breathing zones were 1220±694 ng/m3 for the paver operators; 1360±575 ng/m3 for the roller operators’ and 139±135 ng/m3 for the traffic controllers’. The results show that the more consistent hazard for asphalt workers’ health is derived from exposure to airborne PM10 both in exposed and in non-exposed (controls) workers.